Pengaruh Pembersih Lidah (Tongue Scraper) Terhadap Populasi Candida albicans Di Rongga Mulut - Tri Yatmi Putri; Andi Triawan (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2007)
Tongue scraper (tongue cleaner) might become adding alternative to care teeth and mouth healthy besides toothbrush, especially for yeast Candida albicans. Research objective is to know the inﬂuence of tongue scraper to reduce Candida albicans populations in oral cavity. The research was done by in vivo laboratory experimental to Candida albicans populations in oral cavity. Twenty students which were taking by using accidental sampling method had been selected to do two treatments during two days successively. First day: toothbrusing two times and second day: toothbrusing ones time plus tongue scraper: Research results showed Candida albicans populations total before and after toothbrusing to times with before and after toothbrusing ones time plus tongue scraper are decrease. Based on the statistical analysis with Mann- Whitney test = 0, 05) there was significant difference between Candida albicans populations total before and after toothbrusing to times with before and after toothbrusing ones time plus tongue scraper: Research conclusion is Using tongue scraper has inﬂuence to reduce Candida albicans populations in oral cavity.